MGM561 - Statistical Methods for Research February 2021 - PPSM, Pusat Pengajian Sains Matematik (Pusat Pengajian Sains Matematik, 2021)
Please check that this examination paper consists of SEVEN (7) pages of printed material before you begin the examination. Instructions : Answer SIX (6) questions.